-1
$\begingroup$

I'm really not sure how to solve these type of questions could somebody lead me in the right direction?

  1. Find a closed form for these generating functions

$$(a)\quad u_n = 3n^2+4n+5 \quad for \quad n=0,1,2,... $$ $$(b) \quad u_n = {n+7 \choose4} \quad for \quad n=0,1,2,...$$

$\endgroup$

closed as off-topic by Did, Claude Leibovici, Yiorgos S. Smyrlis, daw, kjetil b halvorsen May 11 '15 at 10:27

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Did, Claude Leibovici, Yiorgos S. Smyrlis, daw, kjetil b halvorsen
If this question can be reworded to fit the rules in the help center, please edit the question.

2
$\begingroup$

The trick is usually to use the formula $$ \sum_{n=0}^\infty \binom{n+k}{k} x^n = \frac{1}{(1-x)^{k+1}}. $$ You can express $3n^2+4n+5$ as a linear combination of $\binom{n+2}{2},\binom{n+1}{1},\binom{n+0}{0}$, thereby solving part (a).

You can solve part (b) in a similar way, but there is a shortcut. We know what $\sum_{n=0}^\infty \binom{n+4}{4} x^n$ equals to. Notice that $$ \sum_{n=0}^\infty \binom{n+7}{4} x^n = \frac{1}{x^3} \sum_{n=0}^\infty \binom{n+7}{4} x^{n+3} = \frac{1}{x^3} \sum_{n=3}^\infty \binom{n+4}{4} x^n = \frac{1}{x^3} \left[ \sum_{n=0}^\infty \binom{n+4}{4} x^n - \sum_{n=0}^2 \binom{n+4}{4} x^n \right]. $$

$\endgroup$
  • $\begingroup$ So for part (a) is the linear combination considered "closed form"? I understand how you got there but i'm not sure why that answers the question $\endgroup$ – Daniel Munoz May 11 '15 at 4:26
  • $\begingroup$ Keep pondering the issue. $\endgroup$ – Yuval Filmus May 11 '15 at 4:29
  • $\begingroup$ It's right in front of me, d'oh! $\endgroup$ – Daniel Munoz May 11 '15 at 4:33
  • $\begingroup$ Last question..for (b) how does the first line work? $\endgroup$ – Daniel Munoz May 11 '15 at 4:42
  • $\begingroup$ The first equality is just multiplying and dividing by $x^3$. The second is substituting $m = n+3$ and then renaming $m$ to $n$. $\endgroup$ – Yuval Filmus May 11 '15 at 4:43
1
$\begingroup$

The first is the generating function $$ \sum_{n=0}^\infty(3\,n^2+4\,n+5)t^n = 3\sum_{n=0}^\infty n^2\,t^n+4\sum_{n=0}^\infty n\,t^n+5\sum_{n=0}^\infty t^n\tag{1} $$ But a bit of calculus and the identity $$ \sum_{n=0}^\infty t^n=\frac{1}{1-t}\tag{2} $$ gives us \begin{align*} \sum_{n=0}^\infty n^2\,t^n&=\frac{t(t+1)}{(1-t)^3} & \sum_{n=0}^\infty n\,t^n&=\frac{t}{(1-t)^2}\tag{3} \end{align*} Can you use (2) to prove (3)? Can you plug the identities from (3) into (1) to obtain the answer?

$\endgroup$

Not the answer you're looking for? Browse other questions tagged or ask your own question.